Place Identity and Heritage as Factors in Establishment of Local Communities. Case of Lithuania - Šutinienė, Irena (Lietuvos istorijos studijos, 2025)
The article, based on the data of an empirical study conducted in Lithuanian village and town communities (involving semi-structured interviews with community representatives), examines the relationship between activities of communities in the field of heritage and their place identity. The links between the place identity of a community and its participation in heritage practices are reciprocal: place identity is an important factor in motivating and mobilizing people to participate in these practices, and heritage is a significant resource in creating place identity, especially such aspects of place identity as feelings of commonality, belonging, ‘rootedness’, continuity of identity, and self-esteem. Emotional aspects of place identity related to local memory and heritage are denoted by a particularly strong motivating and mobilizing power.